Construction of stable packaging cell lines for large-scale industrial BaEV-enveloped retroviral vector production - Zhao, Lijun; Qiu, Chunting; Chen, Hanyi; Yu, Zhuoying; Fan, Jiaqi; Ma, Qihong; Zhan, Sijian; Feng, Yaru; Li, Xiaorui; Ma, Ping; Wang, Weijia; Shi, Yuanyuan; et al. (Frontiers in Immunology, 2025)
IntroductionViral vectors with Baboon endogenous virus (BaEV) envelope proteins have been demonstrated to markedly increase gene transfer efficiency to NK cells. Nevertheless, the cytotoxicity of the BaEV envelope protein necessitates the production of this type of viral vector by transient transfection, which significantly constrains its potential for large-scale industrial application.MethodsIn this study, we constructed a stably packed BaEV-PackRV cell line for BaEVenveloped retroviral vectors. This packaging cell line was constructed to stably express gag, pol, and BaEV envelope proteins, which are essential for retroviral packaging. To this end, we avoided the occurrence of syncytia during virus preparation by knocking out the ASCT-1/2 receptor in the packaging cell line.Results and DiscussionCompared with the existing methods, the transduction efficiency of the retroviral vector produced by BaEV-PackRV was significantly greater in primary immune cells at a lower multiplicity of infection (MOI), and the transduced CAR-T or CAR-NK cells maintained good expansion capacity and enhanced cytotoxicity. On this basis, our system enables large-scale industrial production of BaEV-coated retroviral vectors while significantly reducing costs.This will greatly improve the efficacy of NK cell gene transfer and the effectiveness of related treatments.